2022
DOI: 10.24989/ocg.v341.24
|View full text |Cite
|
Sign up to set email alerts
|

Network Security Threats to Higher Education Institutions

Abstract: The Covid-19 pandemic has significantly changed the way higher education institutions (HEIs) operate around the world. Distance learning has become the unique opportunity that the process further education in conditions where most economic activities were put on hold. To ensure the quality of distance learning have been implemented and used extensively online learning platforms, applications, video conferencing and cloud computing facilities in HEIs. However, this has increased the threats to information secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Studies have shown that a significant percentage of college populations have experienced negative impacts of cyberspace threats, including fear, anxiety, and embarrassment [56]. The COVID-19 pandemic has further increased the threats to information security in higher education institutions, with malware attacks, DoS/DDoS attacks, and phishing attacks being the most common [57]. The active use of IT in various sectors makes corporate information security crucial as cyberattacks can result in significant financial losses and reputational ruin.…”
Section: Cyber Security Threats In Educational Institutionsmentioning
confidence: 99%
“…Studies have shown that a significant percentage of college populations have experienced negative impacts of cyberspace threats, including fear, anxiety, and embarrassment [56]. The COVID-19 pandemic has further increased the threats to information security in higher education institutions, with malware attacks, DoS/DDoS attacks, and phishing attacks being the most common [57]. The active use of IT in various sectors makes corporate information security crucial as cyberattacks can result in significant financial losses and reputational ruin.…”
Section: Cyber Security Threats In Educational Institutionsmentioning
confidence: 99%
“…According to Alexei and Alexei, (2021b), criminals are now interested in collecting students' personal information, which they then utilize in phishing attempts due to hybrid learning. Due to the personal information and data they hold including identity numbers, staff and student intellectual property, higher education institutions are targets of cybercrime (Alexei, 2021a;Fouad, 2021;Fishman et al, 2018). Due to the shift to hybrid learning, these institutions are now targets, which raises the danger and volume of cybersecurity incidents in the sector (Ulven & Wangen, 2021).…”
Section: Interest In Personal Informationmentioning
confidence: 99%
“…According to Maranga and Nelson (2019), higher education institutions in Kenya must deal with issues that include insecure personal areas where employees, teachers and students are allowed to bring their own devices. More than 25% of phishing attacks in the UK's education sector in 2020 targeted university platforms, email, and video conferencing software (Amoresano & Yankson, 2023;Alexei, 2021a). Due to changes in teaching methods, the majority of employees now work from home, which calls for caution because people can become victims of data breaches (Georgiadou et al, 2022).…”
Section: Human Errormentioning
confidence: 99%
“…Thus, cyber security will play an increasingly important role in the activity of HEIs, in the next period. Cyber security has been defined by the International Communications Union (ITU) to mean "a collection of tools, policies, security concepts, security safeguards, guidelines, risk management approaches, actions, training, best practices, assurance and technologies that can be used to protect the cyber environment, and organization and user's assets" [3]. Researchers recommend the implementation of cybersecurity frameworks, to achieve proper protection in the campus network [6], [7].…”
Section: Introductionmentioning
confidence: 99%